Highly sensitive quantification of serum malonate, a possible marker for de novo lipogenesis, by LC-ESI-MS/MS - Akira Honda (Journal of Lipid Research, 2009)
We describe a new sensitive and specific method for the quantification of serum malonate (malonic acid, MA), which could be a new biomarker for de novo lipogenesis (fatty acid synthesis). This method is based upon a stable isotope-dilution technique using LC-MS/MS. MA from 50 μl of serum was derivatized into di-(1-methyl-3-piperidinyl)malonate (DMP-MA) and quantified by LC-MS/MS using the positive electrospray ionization mode. The detection limit of the DMP-MA was approximately 4.8 fmol (500 fg) (signal-to-noise ratio = 10), which was more than 100 times more sensitive compared with that of MA by LC-MS/MS using the negative electrospray ionization mode. The relative standard deviations between sample preparations and measurements made using the present method were 4.4% and 3.2%, respectively, by one-way ANOVA. Recovery experiments were performed using 50 μl aliquots of normal human serum spiked with 9.6 pmol (1 ng) to 28.8 pmol (3 ng) of MA and were validated by orthogonal regression analysis. The results showed that the estimated amount within a 95% confidence limit was 14.1 ± 1.1 pmol, which was in complete agreement with the observed X0 = 15.0 ± 0.6 pmol, with a mean recovery of 96.0%. This method provides reliable and reproducible results for the quantification of MA in human serum.